Aquatic toxicity and fate of styrene oligomers in the environment - Bum Gun Kwon (Ecotoxicology and Environmental Safety, 2023)
Styrene oligomers (SOs) are ubiquitous contaminants that appear in the environment, sometimes to significant extent (see section 3.1). Despite the ongoing international debate on the human health risks posed by SOs, to the best of my knowledge, there are no studies on the aquatic toxicity and environmental fates (biodegradation and atmospheric degradation) of SOs in the environment. This study is to predict the aquatic toxicity and environmental fate of SOs by using the US EPA EPI suite program as an in-silico method. For better understanding, the risks and fates of SOs are compared with those of the well-known bisphenol A (BPA) and styrene monomer (SM or styrene). As a result of this study, SOs are predicted to be relatively more toxic than BPA and SM to aquatic and terrestrial organisms in the freshwater, marine, and terrestrial environments. In particular, the biodegradability of SOs is predicted to be relatively very slow in the environment, and most SOs are more likely to be effectively decomposed by hydroxyl radicals than by ozone in the atmosphere. As a result, this study can contribute to motivating understanding of the aquatic toxicity and fate of ubiquitous SOs in the environment.